PENGARUH KECERDASAN EMOSIONAL, KEDISIPLINAN DAN KOMPENSASI TERHADAP KINERJA PEGAWAI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN GIANYAR - Dewa Gde Ady Wiadnyana; Gede Gama; Putu Agus Eka Rismawan (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2021)
To achieve goals, OPD must be able to optimize the performance of its employees. The factors that affect employee performance are intelligence, emotional intelligence, discipline and compensation. Therefore, this study aims to test and explain the intelligence, discipline and performance compensation of employees at the Investment Service and One Stop Services, Gianyar Regency. The research was conducted at the Investment Service and One Stop Integrated Services, Gianyar Regency, with a total population of 61 employees. The sampling technique used was saturated sample, All data were analyzed using descriptive statistical analysis and inferential statistical analysis. The results showed that emotional intelligence, discipline and positive and significant impact on employee performance. However, the results of the study also show that discipline has a dominant influence in improving employee performance in the Investment and One Stop Integrated Services Office, Gianyar Regency.